Identifying motivation through behavioral regulators and basic psychological needs of Filipino indoor climbers - Katigbak, Joseph Francis V. 2000-
There is a declining trend of physical activity participation among Filipinos. Therefore there is a need for a way to improve the motivation of Filipinos to participate in different physical activity modalities. Indoor climbing has been seen as a possible solution since there has been an increase in the number of people practicing it throughout the country. Using a descriptive research design that is grounded in the Self-Determination Theory, the study aims to identify the behavioral regulators and basic psychological needs that affect sporting participation of Filipino indoor climbers. Fifty-seven indoor climbers from Metro Manila were selected as respondents of the study and all respondents satisfy the criteria for participation set by the researcher. Using descriptive statistics and the Mann-Whitney U test, the researcher was able to describe the different behavioral regulations and basic psychological needs of these climbers. Intrinsic regulation was found to be the primary behavioral regulator of Filipino indoor climbers to participate in the sport. Among the basic psychological needs, the findings of the study found that competence and relatedness of frequent climbers had a statistically significant difference. Indoor climbers are motivated to improve themselves and to continue to be a part of a climbing community. The results of the study found that Filipino indoor climbers are intrinsically motivated to participate in the sport because they satisfy their psychological needs. This finding highlights that Filipino climbers value the bonds that they share with their family, friends, and especially the community